2017
DOI: 10.1038/ng.3883
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic TRIP13 mutations predispose to Wilms tumor and chromosome missegregation

Abstract: Through exome sequencing we identified six individuals with biallelic loss-of-function mutations in TRIP13. All six developed Wilms tumor. Constitutional mosaic aneuploidies, microcephaly,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
140
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(144 citation statements)
references
References 27 publications
4
140
0
Order By: Relevance
“…The identification of germline TRIM28 variants in individuals with Wilms tumors is of high clinical significance. Currently, germline genetic testing of individuals with Wilms tumors is performed mainly in individuals with high‐risk histological subtypes, bilateral tumors, syndromic features, or a family history of cancer . Our findings indicate that genetic screening should also be extended to individuals with tumors with epithelial predominant histology, since it is particularly this rare subgroup of patients representing 4.5% of the total group of patients with Wilms tumors, that appears to harbor germline TRIM28 mutations.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The identification of germline TRIM28 variants in individuals with Wilms tumors is of high clinical significance. Currently, germline genetic testing of individuals with Wilms tumors is performed mainly in individuals with high‐risk histological subtypes, bilateral tumors, syndromic features, or a family history of cancer . Our findings indicate that genetic screening should also be extended to individuals with tumors with epithelial predominant histology, since it is particularly this rare subgroup of patients representing 4.5% of the total group of patients with Wilms tumors, that appears to harbor germline TRIM28 mutations.…”
Section: Discussionmentioning
confidence: 87%
“…Currently, germline genetic testing of individuals with Wilms tumors is performed mainly in individuals with high-risk histological subtypes, bilateral tumors, syndromic features, or a family history of cancer. 6,46 Our findings indicate that genetic screening should also be extended to individuals with tumors with epithelial predominant histology, since it is particularly this rare subgroup of patients representing 4.5% of the total group of patients with Wilms tumors, that appears to harbor germline TRIM28 mutations. Another important finding is the loss of TRIM28 protein expression in tumor cells, which highlights the significance of the inclusion of TRIM28 immunohistochemical staining in the standard pathological analysis of Wilms tumors.…”
Section: Discussionmentioning
confidence: 88%
“…Defects in the mitotic checkpoint, also known as the spindle assembly checkpoint (SAC), a cellular surveillance mechanism that ensures mitosis cannot complete until all chromosomes are correctly attached to the mitotic spindle, have also been proposed to contribute to CIN. For example, mutant or deregulated key checkpoint genes have been found in some cancers (Cahill et al 1998, Hernando et al 2004, Ryan et al 2012, and certain cancer predisposition syndromes such as mosaic variegated aneuploidy (MVA) are caused by mutations in checkpoint proteins including BubRI (Hanks et al 2004), CEP57 (Snape et al 2011) and recently TRIP13 (Yost et al 2017). The latter study is particularly interesting as it demonstrated a direct link between TRIP13 downregulation and the development of Wilms tumour in children, and furthermore, suggested that the nature of the MVA-causing mutation dictates the likelihood of cancer developing in the patient (Yost et al 2017).…”
Section: Mechanisms Driving Chromosomal Instabilitymentioning
confidence: 99%
“…For example, mutant or deregulated key checkpoint genes have been found in some cancers (Cahill et al 1998, Hernando et al 2004, Ryan et al 2012, and certain cancer predisposition syndromes such as mosaic variegated aneuploidy (MVA) are caused by mutations in checkpoint proteins including BubRI (Hanks et al 2004), CEP57 (Snape et al 2011) and recently TRIP13 (Yost et al 2017). The latter study is particularly interesting as it demonstrated a direct link between TRIP13 downregulation and the development of Wilms tumour in children, and furthermore, suggested that the nature of the MVA-causing mutation dictates the likelihood of cancer developing in the patient (Yost et al 2017). Functional experiments in cancer cell lines have demonstrated that the mitotic checkpoint retains activity in some cancer cell lines (Gascoigne & Taylor 2008, Burrell et al 2013 but not others (Ryan et al 2012); therefore, mitotic checkpoint dysfunction is unlikely to fully explain cancer CIN.…”
Section: Mechanisms Driving Chromosomal Instabilitymentioning
confidence: 99%
“…These indel mutations in protein-coding regions cause frameshifts to generate a null-mutant cell. To date, many disease-model cells generated by this strategy have been reported [53][54][55][56][57]. In the field of human genetics, these null-mutant cells are also used in complementary tests for the candidate variants underlying a genetic disorder called by forward genetics approach.…”
Section: Gene Knockout In Human Cultured Cellsmentioning
confidence: 99%